O comportamento da vítima na aplicação da pena entre o Direito Penal e os Direitos Humanos - Cardoso, Lucas Andre Netto (2017)
The research undertaken analyses the behaviour of victims of crimes in the application of the penalty through the perspective of Criminal Law and Human Rights Law. It covers the construction of the international architecture of human rights protection, and the simultaneous development of victimology studies, that are a result of the atrocities committed in the Second World War, listing international instruments which provide for the tutelage of victims of crimes and the influence of these instruments in the Brazilian juridical order. The research then analyses the penalty and the historical treatment of the victim, selecting the work of philosophers of the Antiquity, Middle Ages, Modern Ages and Contemporaneous Age. As a result, it discusses the victim's behaviour vis-a-vis the penalty fixation in the Brazilian legal system, demonstrating the risks to the victim’s rights and the presence of elements of a patriarchal past. Based on such premises, the work looks at the treatment given to victims with regard to the penalty application by international norms and legal doctrine, proposing criticisms to find effectivity to the human rights of victims of crimes